Symulacyjna metoda wyceny wieloczynnikowych opcji rzeczywistych - Wiśniewski, Tomasz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Paper examines concept of specific method of real option valuation based on simulation approach. Monte Carlo simulation is proposed by Copeland and Antikarov to resolve the problem of many uncertainty factors influencing the project. In the next step typical option valuation techniques could be used - Monte Carlo simulation being one of them. The proposal of the author is to simulate the expected value of the project in two steps. In the first step Monte Carlo simulation will calculate the base value of the project without option and the second simulation will calculate the expected value of the project with option. To achieve this the valuation model used for the second simulation have to imitate response of the company to changing environment in that way as the real option is actually exercised. The example of calculation is included and the basic advantages and difficulties are analysed. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 2, s. 357-367